2007
DOI: 10.1097/01.olq.0000225325.23340.a3
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections and Risk Factors Among Truck Stand Workers in Dhaka, Bangladesh

Abstract: Objective-This study was conducted to determine the prevalence of selected sexually transmitted infections (STIs) and their risk factors among workers in and near a truck stand in Dhaka, Bangladesh.Study Design-A random sample of 696 men and 206 women were recruited into a cross-sectional study using a census that enumerated transport agents, motor mechanics, laborers, and vendors in Tejgaon truck stand.Results-The prevalence rates of syphilis (rapid plasma reagin and Treponema pallidum hemagglutination), gono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…6 Studies in the country have found high HIV (2-13 %) and high STI prevalence (3-16 %) among long distance truck drivers. 4,11,12 Therefore the present study aimed to examine the risk behaviors and Prevalence of STI's among Long distance truck drivers in association with their age, education, length of time away from home and CSW's exposure.…”
Section: In 21mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies in the country have found high HIV (2-13 %) and high STI prevalence (3-16 %) among long distance truck drivers. 4,11,12 Therefore the present study aimed to examine the risk behaviors and Prevalence of STI's among Long distance truck drivers in association with their age, education, length of time away from home and CSW's exposure.…”
Section: In 21mentioning
confidence: 99%
“…The sexual behavior of trucking populations has been associated with the transmission of sexually transmitted infections (STI's) and HIV in India and elsewhere in Asia, Africa, South America and the United States. [1][2][3][4][5][6][7][8][9] The most of incidence of HIV and STI occurs in places where trucks are loaded and unloaded, or where truck drivers stop to have their documentation inspected (which can take a considerable length of time). 10 The truck drivers, due to the itinerant nature of their occupation and being far away from their families for a long time tend to have multiple sexual partners and visit commercial sex workers.…”
Section: In 21mentioning
confidence: 99%
“…In a study conducted with truck stand workers in Dhaka, Bangladesh the prevalence rates of syphilis and gonorrhea among men was observed to be 4.1 and 7.7%, respectively (Alam et al 2007). Among hotelbased sex workers, a total of 8.5% had syphilis and 86.8% proved positive for at least one reproductive tract infection (RTI) or sexually transmitted infection (STI) (Nessa et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria and many other countries of the world, the sexual behaviour of truckers coupled with their low level of education and poor HIV awareness, campaign among them have ranked high as the main cause of the relatively high rate of HIV prevalence among them [3][4][5][6][7][8][9]. In many situations, the truckers, looking for alternative outlets for satisfying their sexual needs and to reduce the loneliness caused by the absence from their families, have been known to visit female sex workers (FSW) quite frequently [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, analysis of survey data among truckers revealed that having more than one sexual partner in the last month, never using a condom with sex workers and ever injected narcotics were significant predictors of sexually transmitted infections (STI) among truckers [8].…”
Section: Introductionmentioning
confidence: 99%